Teachers' Strategies in Teaching Speaking during Pandemic at SMAN 1 Jongkong - Sri Wiyanah; Yuli Heldawati; Muhammad Sarda (Universitas PGRI Yogyakarta, 2022)
In speaking English, students have problems with limited vocabulary, pronunciation accuracy, self-confidence, and others. The teacher's strategy has a lot of influence on improving students' speaking. During this pandemic situation, teacher must apply the appropriate strategy in teaching speaking, since the classroom situation is different. The research aimed to identify the teachers' obstacles in teaching speaking and to find out the teachers' strategies in teaching speaking during pandemic at SMAN 1 Jongkong. The design of this research is the qualitative research which case study. The subjects of this research were two English teachers who teach English in tenth and eleventh grades of SMAN 1 Jongkong. The data of this research were collected by observation, interview, and documentation. The data were analyzed by: data reduction, data display, and drawing conclusion. Then, to point out the trustworthiness of the data, this research used triangulation method. Method triangulation was used in this research to compare the outcomes of interviews and the findings of observations. It means that in checking the data validation, researcher has to compare some method of collecting data that have been used (observation, interview, and documentation) in order that the data collection was in the same place or portion. The result of this research shows that the students found obstacles in learning speaking during pandemic situation, such as problem with internet connection because they were located in remote area which had poor connection and students were mostly passive during the online learning process because they felt ashamed and scared to answer teacher’s question, since they still had to adapt the current learning situation. Therefore, the English teachers applied various strategies to achieve the goals in teaching speaking. The strategies were storytelling, conversation practice, discussion, and translation.